School Library Management in Increasing Students' Interest in Reading - Syaharani, Lely Adiba; Sumarsono, Raden Bambang; Sultoni, Sultoni (Universitas Negeri Malang, 2024)
Education is an essential basic need for the development of individuals and society. In this context, school libraries play an important role as a center of learning resources that support the learning process. This study aims to explore the influence of library services on students' reading interest and the quality of education in schools. Using the literature study method, the results of the study show that effective library service management includes: (1) planning, (2) organizing, (3) implementation, and (4) evaluation can increase students' access to diverse and relevant reading collections. In addition, interactive literacy programs and a comfortable library environment contribute to creating a positive reading culture. Support from schools in building strong literacy policies further strengthens students' interest in reading. Thus, well-managed library services not only support the improvement of students' literacy skills, but also contribute to the overall quality of education. This research emphasizes the importance of strengthening the role of libraries in improving the quality of education in Indonesia.